You're so vein: bundle sheath physiology, phylogeny and evolution in C3 and C4 plants. (20th August 2012) - GRIFFITHS, HOWARD; WELLER, GEORGE; TOY, LYDIA F. M.; DENNIS, ROSS J.
ABSTRACT Bundle sheath (BS) anatomy is found in most C4 lineages, associated with low inter‐veinal distances (IVD) and high BS:mesophyll ratio (BS:MC). The origins, function and selective advantages of the BS in C3 lineages are relevant for understanding the environmental, molecular and phylogenetic determinants of C4 evolution. Suggested functions for BS have included structural support, hydraulic isolation, storage for water, ions, and carbohydrates, and photorespiratory carbon metabolism; we propose a central role for cavitation repair, consistent with the BS as a control centre on regulating stem and leaf hydraulic continuity. An analysis of BS traits in the phylogenetic lineages giving rise to C4 grasses (the 'PACMAD' clade) shows an initial enhancement in BS:MC ratio in C3 lineages, although IVD is similar to the Pooideae sister group. Using a global database, a well‐developed BS in the C3 PACMAD lineages was associated with higher precipitation and temperatures in the habitat of origin on an annual basis, with the C3 to C4 progression defined by the aridity index (AI). Maintaining leaf hydraulic conductance and cavitation repair are consistent with increased evaporative demand and more seasonal precipitation as drivers, first for the C3 BS, and then C4 diversification, under declining CO2 concentrations in the Palaeogene and Neogene.